The Potential of Trichoderma sp. as Biological Agent to Support the Germination of Corn Seeds (Zea Mays) - Betty Lahati; Zauzah Abdullatif; Fatmawati Kaddas; Martini Labaradji (International Journal on Food, Agriculture and Natural Resources, 2021)
This research is motivated by the fact that corn seeds in storage are often characterized with low seed viability and infected by diseases so that the seeds grow abnormally and even die. Corn seeds have thick/hard cell walls. It is acknowledged that the corn seed walls contain cellulose, which can be broken down by microorganisms. One such microorganism is the Trichoderma fungus, which is also a biological agent. This study aims to analyze the effect of the biological agents Trichoderma sp. on corn seed germination and identify the best concentration of Trichoderma sp. against corn seed germination. The corn seeds used in this study were locally grown, which had been stored for 6 months. The seed coating (bio seed coating of local corn) was tested at several concentrations of Trichoderma sp. (treatment), namely without treatment (control), 5g, 10g, 15g, and 20g. Each concentration was repeated 4 times, using several parameters to analyze normal sprouts and germination capacity. The analysis results confirmed the potential of Thrichoderma biological agents on corn seed germination. The T1 treatment with 5g Trichoderma biological agents significantly improve corn seed germination.